The Cost Burden Paradox in Petty Corruption Enforcement: A Socio-Legal Study Based on Cost-Awareness - Sandhy, Andhika Prima; Panjaitan, Hulman (CV. Social Politic Genius (SIGn), 2025)
Law enforcement efforts against petty corruption in Indonesia are currently trapped in a serious economic inefficiency paradox, where case-handling operational costs often far exceed the value of the savings from avoided state losses. This problem is further complicated by norm disharmony between the efficiency spirit in Law Number 1 of 2023 and the rigidity of sectoral regulations effective as of January 2026. This study aims to analyze such inefficiency using the EAL approach and formulate a new Cost-Awareness-based settlement model. The research method applied is socio-legal, synthesizing doctrinal analysis of norm conflicts with secondary data evaluation regarding case cost burdens and social behavior. Research findings reveal that the conventional retributive approach creates a double loss for state finances. Fundamental juridical barriers are identified in the form of a regulatory “double lock”: Article 4 of Law Number 31 of 1999 which closes the material discretion space, and Article 82 letter c of Law Number 20 of 2025 formally excluding corruption from the restorative justice mechanism. To unravel this deadlock, the study recommends a limited double amendment to both articles, the application of financial sanctions in the form of Double Restitution accompanied by administrative sanctions of dismissal, and the strengthening of public oversight through Citizen Auditors. This model is offered as a concrete solution to ensure legal certainty and state budget efficiency.